Capital Structure and Bank Performance in Indonesia's Dual Banking System - Melinda, Vera; Wiliasih, Ranti; Irfany, Mohammad Iqbal; Haq, Daffa Aqomal; Camara, Bumi (SMART Insight, 2024)
The capital structure of a bank is directly tied to the risk and rate of return. The aim of this study is to examine the impact of capital structure on financial performance in Indonesia's dual banking system from the first quarter of 2013 to the third quarter of 2019, using 9 Conventional Commercial Banks (BUK) and 9 Sharia Commercial Banks (BUS) as research samples. Panel data regression is employed in this study, with Return on Assets (ROA) and Return on Equity (ROE) as dependent variables, and Equity to Total Asset Ratio (EAR), Debt to Equity Ratio (DER), company size, and economic growth as independent variables. The findings reveal that EAR, DER, and economic growth all have beneficial and significant effects on conventional commercial banks' ROA and ROE. Company size and economic growth have a positive and significant effect on ROA and ROE, while Sharia Commercial Banks, EAR, and DER have a negative and significant effect on ROA and ROE. These findings indicate that capital structure has a sometimes beneficial impact on financial success.